Geometric Design for Damar Wulan Road Deli Serdang Regency - Tetra Oktaviani; Falwan Rizky Gunawan (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Damar Wulan Road is one of the 3.5 km road sections located in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. This road has the potential to be an access to a strategic location, but there are still few people who use Damar Wulan Road as a mobilization route because most of the road is still subgrade. Therefore, it is necessary to design the Damar Wulan Road so that it can be used by the community. This study aims to design vertical alignment for Damar Wulan Road. The method used for vertical alignment design is TPGJAK 1997. The calculation on the vertical alignment obtained results in the form of 16 PVI arches, which are 8 convex vertical curves and 8 concave vertical curves.